Heterogeneous genetic basis of age at maturity in salmonid fishes. Issue 6 (8th March 2021) - Waters, Charles D.; Clemento, Anthony; Aykanat, Tutku; Garza, John Carlos; Naish, Kerry A.; Narum, Shawn; Primmer, Craig R.
Abstract: Understanding the genetic basis of repeated evolution of the same phenotype across taxa is a fundamental aim in evolutionary biology and has applications in conservation and management. However, the extent to which interspecific life‐history trait polymorphisms share evolutionary pathways remains underexplored. Here, we address this gap by studying the genetic basis of a key life‐history trait, age at maturity, in four species of Pacific salmonids (genus Oncorhynchus ) that exhibit intra‐ and interspecific variation in this trait—Chinook Salmon, Coho Salmon, Sockeye Salmon, and Steelhead Trout. We tested for associations in all four species between age at maturity and two genome regions, six6 and vgll3, that are strongly associated with the same trait in Atlantic Salmon ( Salmo salar ). We also conducted a genome‐wide association analysis in Steelhead to assess whether additional regions were associated with this trait. We found the genetic basis of age at maturity to be heterogeneous across salmonid species. Significant associations between six6 and age at maturity were observed in two of the four species, Sockeye and Steelhead, with the association in Steelhead being particularly strong in both sexes ( p  = 4.46 × 10 −9 after adjusting for genomic inflation). However, no significant associations were detected between age at maturity and the vgll3 genome region in any of the species, despite its strong association with the same trait in Atlantic Salmon. We discuss possible explanations for the heterogeneous nature of the genetic architecture of this key life‐history trait, as well as the implications of our findings for conservation and management.